Pendampingan Peningkatan Human Capital Melalui Eksplorasi Dimensi Visual di Kampung Tridi, Malang - Adya Hermawati; Choirul Anam; Mulyono; Angga Eka Alfianto; Dani Riyadi; Ayu Siti Ni’mah Syuridiniah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Tridi Village is a village located in Malang City, Indonesia, which is famous for the uniqueness and beauty of the 3D wall paintings that decorate the entire village. These paintings create an interesting visual atmosphere, reflecting local art, culture and traditions. Tridi Village has become a popular tourism destination that attracts tourists with its unique charm. Apart from the wall art, this village also has cultural heritage and local crafts which are an additional attraction. Increasing tourism attractiveness through innovative digital marketing strategies is expected to have a positive impact on economic growth and welfare of the people of Tridi Village. This research explores the application of creative thinking methods in developing digital marketing strategies to increase the tourism attractiveness of Kampung Tridi. Through brainstorming and mind mapping sessions, the people of Kampung Tridi are actively involved in generating innovative ideas related to the potential of tourism, arts and local culture. Brainstorming sessions create a collaborative space without critical boundaries, while mind mapping graphically visualizes the relationships between ideas. The result is an integrated digital marketing strategy, designed to increase tourist visits and empower the local economy. Implementation of this strategy requires active community involvement and full support from the local government.